HUBUNGAN ANTARA SELF EFFICACY DENGAN KESEJAHTERAAN PSIKOLOGIS CAREGIVER DALAM MERAWAT LANSIA SKIZOFRENIA DI RSJ Dr. RADJIMAN WEDIODININGRAT LAWANG MALANG: The Relationship of Self Efficacy with the Caregiver’s Psychological Well Being Who Taking Care for Elderly Schizophrenia at Psychiatric Hospital Dr. Radjiman Wediodiningrat Lawang Malang - Roudlotul Jannah; Joni Haryanto; Yanis Kartini (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Background: The increasing number of elderly with schizophrenia in the world is growing rapidly. Abaout one from seven schizophrenic clients is older than 65 years old. Elderly with schizophrenia caused more complete problems related to diseases and aging process. The burden felt by the caregiver during caring for the patient will have an impact on the psychological well-being of the caregiver, indirectly will result in the low quality life of caregiver and the low quality of care provided to the patient. Objective: to determine the relationship between self efficacy and the psychological well-being of caregivers who taking care for elderly schizophrenia. Method: this study is a quantitative study with a cross sectional design. Samples were 88 respondets, taken by systematic random sampling according to inclusion and exclusion criteria. Data were analysis using correlation and chi square with a significance level of 95%. Results: result of the study showed that the majority of caregivers aged 26-45 years (adults) were 58 respondents (65.9%), female as many as 53 respondents (60.2%), had senior high school education levels as many as 37 respondents (42%) , income status less than Rp. 1,851,083 as many as 53 respondents (60.2%), relationship with patients was children as many as 52 respondents (59.1%). Conclusion: Self efficacy is very important for caregivers, with good efficacy will affect the readiness of caregivers to solved difficult situations that are stressful and stressful during treatment so that psychological well-being remains good even though the complexity of problems is faced while providing care for elderly schizophrenia. Keywords : self efficacy, caregiver, skizofrenia, elderly, psychological well being